Abeliophyllum distichum Ameliorates High-Fat Diet-Induced Obesity in C57BL/6J Mice by Upregulating the AMPK Pathway - Eom, Ji (Nutrients, 2020)
The use of natural compounds as anti-obesity agents has been gaining attention over the past few years. Abeliophyllum distichum Nakai is endemic to Korea. In the present study, an A. distichum leaf extract (AE) was analyzed for its anti-obesity effects in mice fed a high-fat diet. Seven-week-old male C57BL/6J mice were divided into five groups, namely, normal diet (ND), high-fat diet (HD), HD + Garcinia (GE300), HD + AE low dose (AE100), and HD + AE high dose (AE300). After 8 weeks of the experimental period, treatment with AE reduced body weight and ameliorated high-fat diet-induced changes in serum lipid levels. Histological analysis revealed that treatment with AE decreased lipid accumulation in the liver and brown adipose tissue. Also, AE reduced the adipocyte size in epididymal fat. The reduction in adipose tissue mass in the AE-treated groups was clearly visible in micro-computed tomography images. The expression levels of lipogenic genes, such as PPARγ, C/EBPα, ACC, and FAS, were significantly reduced in the AE300 group. The levels of p-AMPK and p-ACC were increased in the AE300 group compared to the HD group, indicating that the anti-obesity effect of AE was mediated through the AMPK pathway.